Molecular characterization of Salmonella spp. and Listeria monocytogenes strains from biofilms in cattle and poultry slaughterhouses located in the federal District and State of Goiás, Brazil - Emilia Fernanda Agostinho Davanzo (Public Library of Science (PLoS), 2021)
Listeria monocytogenes and Salmonella spp. are considered important foodborne pathogens that are commonly associated with foods of animal origin. The aim of this study was to perform molecular characterization of L. monocytogenes and Salmonella spp. isolated from biofilms of cattle and poultry slaughterhouses located in the Federal District and State of Goiás, Brazil. Fourteen L. monocytogenes isolates and one Salmonella sp. were detected in poultry slaughterhouses. No isolates were detected in cattle slaughterhouses. All L. monocytogenes isolates belonged to lineage II, and 11 different pulsotypes were detected. Pulsed-field gel electrophoresis analysis revealed the dissemination of two strains within one plant, in addition to the regional dissemination of one of them. The Salmonella isolate was identified via whole genome sequencing as Salmonella enterica serovar Minnesota ST548. In the sequence analysis, no premature stop codons were detected in the inlA gene of Listeria. All isolates demonstrated the ability to adhere to Caco-2 cells, while 50% were capable of invading them. Antimicrobial resistance was detected in 57.1% of the L. monocytogenes isolates, and resistance to sulfonamide was the most common feature. The tetC, ermB, and tetM genes were detected, and four isolates were classified as multidrug-resistant. Salmonella sp. was resistant to nine antimicrobials and was classified as multidrug-resistant. Resistance genes qnrB19, blaCMY-2, aac(6’)-Iaa, sul2, and tetA, and a mutation in the parC gene were detected. The majority (78.5%) of the L. monocytogenes isolates were capable of forming biofilms after incubation at 37°C for 24 h, and 64.3% were capable of forming biofilms after incubation at 12°C for 168 h. There was no statistical difference in the biofilm-forming capacity under the different evaluated conditions. Salmonella sp. was capable of forming biofilms at both tested temperatures. Biofilm characterization was confirmed by collecting the samples consistently, at the same sampling points, and by assessing biofilm formation in vitro. These results highlight the potential risk of cross-contamination in poultry slaughterhouses and the importance of surveillance and pathogen control maintenance programs within the meat production industry.